PENERAPAN PEMBELAJARAN KONTEKSTUAL PADA MATA PELAJARAN MATEMATIKA UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA SMA - Sisca Rahmadonna (MAJALAH ILMIAH PEMBELAJARAN, 2011)
The purpose of this research is to find out about: 1) How Mathsubject for the eleventh grade science class is taught using contextuallearning approach; and 2) Whether contextual learning approach canimprove student’s motivation in learning the subject.This is an action research using several learning methods suchas group discussion and presentation. The data is gathered fromobservation, interview, questionnaire, test and documentation.From this research we find that contextual learning can beapplied for the eleventh grade science class using the seven componentof contextual learning approach: constructivism (Constructivism), ask(Questioning), find (Inquiry), community learning (LearningCommunity), modeling (modeling), reflection (Reflection) andassessment of the actual (Authentic Assessment). The research showsimprovement in student’s learning motivation – the improvement afterthe first cycle is categorized as medium and after the second cycle ishigh, in which all students’ test result is satisfactory. From thisresearch, we conclude that contextual learning approach, whenimplemented correctly, can improve students’ motivation in learningmath subject.